Exploiting exo and endo furan-maleimide Diels–Alder linkages for the functionalization of organoruthenium complexes. Issue 6 (11th January 2022) - Tran, Hoang-Van; Haghdoost, Mohammad Mehdi; Poulet, Sylvain; Tcherkawsky, Paul; Castonguay, Annie
Abstract : Given the promising advances of organoruthenium complexes in therapy, the possibility of exploiting furan-maleimide Diels–Alder linkages as a mean to modulate their biological properties was explored. Abstract : Diels–Alder cycloadditions involving furans and maleimides are extensively used in organic chemistry and materials synthesis. Given the promising advances of organoruthenium complexes in therapy, we explored the possibility of exploiting such Diels–Alder linkages as a mean to modulate their biological properties.